2017
DOI: 10.1038/s41598-017-07557-2
|View full text |Cite
|
Sign up to set email alerts
|

Descemet’s Membrane Supports Corneal Endothelial Cell Regeneration in Rabbits

Abstract: Descemet’s membrane (DM) helps maintain phenotype and function of corneal endothelial cells under physiological conditions, while little is known about the function of DM in corneal endothelial wound healing process. In the current study, we performed in vivo rabbit corneal endothelial cell (CEC) injury via CEC scraping, in which DM remained intact after CECs removal, or via DM stripping, in which DM was removed together with CECs. We found rabbit corneas in the CEC scraping group healed with transparency rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 30 publications
5
23
0
Order By: Relevance
“…For that purpose, we established and compared two corneal endothelial dysfunction models: DM stripping and EC stripping. Consistent with a recent report,26 we showed that DM stripping has a more dramatic effect inducing corneal edema than only removing the ECs in a similar area. All 5.5 mm DM-stripped control animals recovered by day 21 or 28.…”
Section: Discussionsupporting
confidence: 93%
“…For that purpose, we established and compared two corneal endothelial dysfunction models: DM stripping and EC stripping. Consistent with a recent report,26 we showed that DM stripping has a more dramatic effect inducing corneal edema than only removing the ECs in a similar area. All 5.5 mm DM-stripped control animals recovered by day 21 or 28.…”
Section: Discussionsupporting
confidence: 93%
“…For induction of corneal endothelium, the induced HCEC expressed cytoplasmic γ-tubulin and junctional p120, N-cadherin, α-catenin, β-catenin, Zona occludens protein 1 (ZO-1) and Na-K-ATPase, all of which are markers of HCEC [1,26], suggesting TM cells could be induced to HCEC-like cells. Such expression of HCEC markers was consistent with the in vivo expression pattern previously reported by us [26][27][28][29][30][31][32][33][34]. The reprogrammed cells on 3D Matrigel had a significantly higher frequency of adipocytes stained by Oil Red O than cells cultured on coated Matrigel, suggesting the cells on 3D Matrigel were more potent than the cells on Matrigel coated-plastics for induction of adipocytes [1].…”
Section: Ivyspringsupporting
confidence: 90%
“…In this survey, a pre-Descemet membrane corneal opacity identified in a NZW rabbit by slit lamp biomicroscopy and OCT (data not shown) was similar to those previously described. 61 These sporadic findings appear to be a degenerative or traumatic change that may be related to the lifelong proliferative capacity of corneal endothelial cells in rabbits 68,69 and rodents that is absent in most mammals. Although pre-Descemet corneal dystrophy reported in humans is still included in the IC3D classification, 31 this opacity is also of uncertain heritability in humans and may be a degenerative or age-related change similar to that reported in NZW rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit is one species in which corneal endothelium divides throughout life and their endothelium may even form multinucleated cells. 68,69 Endothelial dystrophies (4 subtypes). Three of the endothelial dystrophies including Fuchs endothelial corneal dystrophy (FECD), posterior polymorphous corneal dystrophy (PPCD), and congenital hereditary endothelial dystrophy (CHED) share gene mutations.…”
Section: Comparative Literature Review Of Corneal Dystrophy In Animalmentioning
confidence: 99%